The ACE D/D genotype is protective against the development of idiopathic deep vein thrombosis and pulmonary embolism - Wells, Philip S.; Rodger, Marc A.; Forgie, Melissa A.; Langlois, Nicole J.; Armstrong, Linlea; Carson, Nancy L.; Jaffey, James (Thrombosis and Haemostasis, 2003)
The deletion/deletion (D/D) genotype of the angiotensin converting enzyme (ACE) has been purported to be a risk for postoperative thrombosis. This D/D genotype has not been evaluated as a risk factor for idiopathic venous thromboembolism (VTE).The primary objective of the present study was to determine whether the D/D genotype of ACE is independently associated with the occurrence of idiopathic venous thromboembolic disease.We prospectively enrolled consecutive patients with at least one objectively confirmed idiopathic VTE. Friends of cases were recruited as controls and matched to cases by sex, ethnicity, and age. Patients were tested for the ACE I/D polymorphism in addition to factor V Leiden, prothrombin G20210A, and factor VIII levels.Three hundred cases and 300 controls were enrolled; 97% were Caucasian. There were 148 females and 152 males in each group with a mean age of 56.21 years (SD=15.33). The ACE D/D genotype was present in 25.3% of cases and 32.4% of controls for an adjusted odds ratio of 0.66 (95% CI = 0.433 to 0.997). We can conclude that the ACE D/D genotype is protective against idiopathic venous thromboembolism.
Keywords: ACE; angiotensin converting enzyme; venous thromboembolism; deep vein thrombosis; pulmonary embolism